Failure of 150 KV Power Transformer in Indication of Dissolved Gas Analysis Test in Total Dissolved Combustile Gas (TDCG) Method - Irwanto Irwanto (VANOS Journal of Mechanical Engineering Education, 2021)
A transformer is an electrical device to change the voltage from one level to a certain level with the same frequency that is generated from the generator. This transformer is used in a power plant to increase the voltage from the generator to be supplied to extra high voltage substations. By knowing the type and amount of gas in the transformer oil, it can be seen that the failure occurred. Preventive steps can be taken before the transformer is more severely damaged or a breakdown which will result in disrupted and detrimental electrical energy supply. The method used in this research is data collection methods used are observation, interviews and participation conducted at PT. Krakatau, Serang Banten. The method used to determine the failure of the transformer is the Dissolved Gas Analysis (DGA) method. The DGA test uses several methods to interpret the data, these methods are Total Dissolved Combustile Gas (TDCG), Key Gasses, Doernenburg Ratio, Roger's Ratio, IEC Ratio and Duval's Triangel. The method used in this research is direct observation of the process of taking transformer oil samples and testing transformer oil samples with the Transport-X tool. The result of this research is that the transformer condition is still in normal condition, because the appearance of CO2 gas has almost crossed the condition limit,so other supporting methods are needed to find the cause of the gas. Key gasses indicate the presence of overheating of paper insulation, IEC Ratio diagnoses transformer failure caused by heat failure at temperatures of 300o-700o C, Duval's Triangel diagnoses transformer failure caused by temperatures over 700o and this method supports the previous analysis. With this method, overheating occurs at certain points (hotspots) in the internal transformer. Preventive maintenance is needed to conform to the standard of the transformer.A transformer is an electrical device to change the voltage from one level to a certain level with the same frequency that is generated from the generator. This transformer is used in a power plant to increase the voltage from the generator to be supplied to extra high voltage substations. By knowing the type and amount of gas in the transformer oil, it can be seen that the failure occurred. Preventive steps can be taken before the transformer is more severely damaged or a breakdown which will result in disrupted and detrimental electrical energy supply. The method used in this research is data collection methods used are observation, interviews and participation conducted at PT. Krakatau, Serang Banten. The method used to determine the failure of the transformer is the Dissolved Gas Analysis (DGA) method. The DGA test uses several methods to interpret the data, these methods are Total Dissolved Combustile Gas (TDCG), Key Gasses, Doernenburg Ratio, Roger's Ratio, IEC Ratio and Duval's Triangel. The method used in this research is direct observation of the process of taking transformer oil samples and testing transformer oil samples with the Transport-X tool. The result of this research is that the transformer condition is still in normal condition, because the appearance of CO2 gas has almost crossed the condition limit, so other supporting methods are needed to find the cause of the gas. Key gasses indicate the presence of overheating of paper insulation, IEC Ratio diagnoses transformer failure caused by heat failure at temperatures of 300o-700oC, Duval's Triangel diagnoses transformer failure caused by temperatures over 700o and this method supports the previous analysis. With this method, overheating occurs at certain points (hotspots) in the internal transformer. Preventive maintenance is needed to conform to the standard of the transformer.